An Improvement of Network Routing Protocol with K-Means Clustering for Reactive Wireless Sensor Networks - Thanaphat Arjinwat (2022)
Wireless sensor networks (WSNs) are currently used in many areas for monitoring environmental parameters. It is usually deployed in hard-to-access areas and batteries cannot be replaced. WSN components must be designed for energy efficiency for both hardware and software. A routing protocol is needed to manage the network and help extend network lifetime. This work addresses the WSN protocol for reactive networks by aiming to develop a clustering method, which is a huge impact on energy consumption in the routing protocol. K-Means algorithm is deployed for efficiency sensor nodes clustering. The cluster head selection is done based on the maximum remaining energy node in each cluster. Simulation is performed to demonstrate the performance of the proposed scheme. The simulation results show that the proposed scheme has better performance than ordinary protocols and able to extend network lifetime. The characteristics of the proposed scheme are verified by using different sample datasets as well.